Parvati in penance - Temples of India Project Team (Jio Institute, 2024)
Inside the sanctum of the temple are preserved beautiful sculptures of nayikas on the wall, while at the centre of the principal/back wall, there is a colossal image of Parvati in penance or the pancagni tapa. Interestingly, their names are scribed in the 10th-century Kutila script. The inscribed epithet calls her vikata, a possible explanation for this unusual name would be Gauri treading the vikata-marga by performing penance. Interestingly, the unusual epithet, Vikata, also appears in the Harsha stone inscription of VS 1030. Shiva, who occupies a central place in the sanctum in the form of a linga placed on yoni, is coupled with the representation of Shakti on the surrounding walls inside the sanctum. A four-armed Parvati is performing the penance of the pancagni tapa, also shown visually depicted with fires on either side. She stands erect on an iguana and hence has been labelled as Godhasana Gauri. On either side are two standing and two sitting female attendants.